2007
DOI: 10.1111/j.1398-9995.2007.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of total IgE levels on the severity of sting reactions in Hymenoptera venom allergy

Abstract: Patients with Hymenoptera venom allergy and high levels (>250 kU/l) of total IgE, predominantly develop grade I and grade II reactions and appear to be protected from grade III reactions. However, this hypothesis should be confirmed by extended studies with sting challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
75
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 31 publications
8
75
1
7
Order By: Relevance
“…Several studies which investigated the association of total or sIgE levels and skin test results with severe SR did not find a significant relationship among those parameters [19,27,28,40]. Total IgE levels significantly correlated with sIgE levels in our study (data not shown).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several studies which investigated the association of total or sIgE levels and skin test results with severe SR did not find a significant relationship among those parameters [19,27,28,40]. Total IgE levels significantly correlated with sIgE levels in our study (data not shown).…”
Section: Discussionsupporting
confidence: 60%
“…Some authors have determined male sex as a risk factor for severe SRs [17,26], whereas a considerable number of studies could not find a difference between genders [11,21,27,28]. Results of a recent study on British beekeepers revealed female sex as a predisposing factor for severe SR [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the frequency of bee and wasp sensitization was nearly the same, although approximately two thirds of the subjects had been stung by wasps. This is in contrast to the general population of Hymenoptera venom-allergic patients in Austria, who are mainly sensitized to wasp venom (73%) [10]. Thus, one might speculate that these asymptomatic sensitizations might originate from other sources than a Hymenoptera sting.…”
Section: Discussionmentioning
confidence: 71%
“…22,36 Development of urticaria/angioedema might subsequently be inhibited by counterregulatory release of endogenous epinephrine leading to peripheral vasoconstriction. 25,33 Short time interval between sting and onset of symptoms…”
Section: The Density Of Cardiac Mast Cells Is Increased In the Settingmentioning
confidence: 99%